Details of the recurrent and capital expenditure of the 2006 appropriation act - Federal Republic of Nigeria; Federal Republic of Nigeria (Abuja Budget Office of the Federal Ministry of Finance, 2005)
Details of the recurrent and capital expenditure of the 2006 appropriation act..
Vol.I: 2006 fiscal year
osa; 04/07/18
Loans
Keywords: Budget; Nigeria